2016
DOI: 10.3389/fpsyg.2016.00963
|View full text |Cite
|
Sign up to set email alerts
|

3-Year-Old Children Selectively Generalize Object Functions Following a Demonstration from a Linguistic In-group Member: Evidence from the Phenomenon of Scale Error

Abstract: The present study investigated 3-year-old children’s learning processes about object functions. We built on children’s tendency to commit scale errors with tools to explore whether they would selectively endorse object functions from a linguistic in-group over an out-group model. Participants (n = 37) were presented with different object sets, and a model speaking either in their native or a foreign language demonstrated how to use the presented tools. In the test phase, children received the object sets with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
1
28
0
3
Order By: Relevance
“…Indeed, when objects are labelled, the incidence of scale errors in tool‐based scale errors scenario increases compared to a non‐labelling condition (Hunley & Hahn, ). In addition, Oláh, Elekes, Pető, Peres, and Király () showed that children were more likely to produce scale errors with tools when object labels were introduced in children's native language as opposed to a foreign language, suggesting that meaningful linguistic information is needed for this facilitation to occur—at least in situations where children are required to act with tools.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when objects are labelled, the incidence of scale errors in tool‐based scale errors scenario increases compared to a non‐labelling condition (Hunley & Hahn, ). In addition, Oláh, Elekes, Pető, Peres, and Király () showed that children were more likely to produce scale errors with tools when object labels were introduced in children's native language as opposed to a foreign language, suggesting that meaningful linguistic information is needed for this facilitation to occur—at least in situations where children are required to act with tools.…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of object names has important consequences for the children's conception of objects, as it influences the way they categorize and individuate objects (e.g., Balaban & Waxman, 1997). Based on the results by Hunley and Hahn (2016), as well as Oláh et al (2016), who showed effects of object labelling on scale errors, and by Grzyb et al (2018) who showed that early talkers tend to produce more errors than late talkers, we expected DDMAN to produce more scale errors when actions were selected via the indirect semantic route (which incorporates a link between object name and action) as compared to when actions were selected via the direct visual route. However, this was not confirmed by the results from our simulation, for two possible reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Erősebben kötődik a funkció a tárgyhoz, ha a saját csoport tagjától tanuljuk? Oláh, Elekes, Peres, Pető & Király (2016) kutatásukban arra keresték a választ, hogy a három éves gyerekek vajon hajlamosabbak lesznek-e az aránytévesztésre, ha látják, amint egy magyar modell követ el aránytévesztést, szemben egy külföldivel?…”
Section: Kitől Tanulnak Inkább a Gyerekek?unclassified
“…Az aránytévesztés fogalma azt takarja, hogy a kisgyermekek figyelmen kívül hagyják egy számukra ismerős kategóriába tartozó tárgy valós méretét -például megpróbálnak beülni egy kisautóba (DeLoache et al, 2004in Oláh et al, 2016. Az aránytévesztés fakadhat abból, hogy az eszköz funkciója is beletartozik kategóriareprezentációjába, így amikor ez a kategóriareprezentáció aktívvá válik, a kisebb gyermekek még nem tudják legátolni a funkció aktivációját is.…”
Section: Kitől Tanulnak Inkább a Gyerekek?unclassified
See 1 more Smart Citation